2008
DOI: 10.1271/bbb.80239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Nukacin KQU-131, a New Type-A(II) Lantibiotic Produced byStaphylococcus hominisKQU-131 Isolated from Thai Fermented Fish Product (Pla-ra)

Abstract: Staphylococcus hominis KQU-131, isolated from Thai fermented marine fish, produces a heat stable bacteriocin. Structural and genetic analysis indicated that the bacteriocin is a variant of nukacin ISK-1, a type-A(II) lantibiotic, and we termed the bacteriocin nukacin KQU-131. There were three different amino acid residues between nukacin ISK-1 and nukacin KQU-131, one residue in the leader peptide and the other two in the mature peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Nukacin L217 is composed of 27 amino acid residues and showed high similarity (two different amino acids) with nukacin KQU-131 produced by Staph. hominis KQU-131 (Wilaipun et al 2008). These highly similar amino acid sequences suggest an important role for nukacin-type bacteriocins produced by different species of CoNS.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Nukacin L217 is composed of 27 amino acid residues and showed high similarity (two different amino acids) with nukacin KQU-131 produced by Staph. hominis KQU-131 (Wilaipun et al 2008). These highly similar amino acid sequences suggest an important role for nukacin-type bacteriocins produced by different species of CoNS.…”
Section: Discussionmentioning
confidence: 85%
“…hominis KQU‐131 (Wilaipun et al . ). These highly similar amino acid sequences suggest an important role for nukacin‐type bacteriocins produced by different species of CoNS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The immunity mechanism against nukacin ISK-1 mediated by NukFEG and NukH has been investigated before (2,(21)(22)(23)39). On the basis of our analysis, we suggested that NukFEG transports both nukacin ISK-1 on the membrane and nukacin ISK-1 captured by NukH (2,22).…”
mentioning
confidence: 74%